1294. Activity of Ceftolozane/Tazobactam and Comparators against Resistant Pseudomonas aeruginosa Isolates from Patients with Respiratory Tract or Bloodstream Infections in ICU and non-ICU settings – SMART United States 2018-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Andrew DeRyke, C; Harris, Kelly; Young, Katherine; Motyl, Mary; Sahm, Daniel F
Abstract: Background: ICUs are considered hotspots of antimicrobial resistance. Treatment of ICU patients with infections caused by P. aeruginosa ( Pa ) is especially challenging. When patients fail to improve on therapy with first-line antipseudomonal agents such as piperacillin/tazobactam (P/T) or cefepime (FEP), clinicians often escalate to a carbapenem. Ceftolozane/tazobactam (C/T) is an antipseudomonal cephalosporin (combined with a β-lactamase inhibitor) that was specifically developed to have enhanced antibacterial activity against Pa . We evaluated the activity of C/T and comparators against Pa isolates collected from patients with respiratory tract (RTI) or bloodstream infections (BSI) in ICU and non-ICU settings. Co-resistance ( e.g ., activity of C/T or meropenem (MEM) when Pa is nonsusceptible (NS) to P/T or FEP) was also evaluated to help inform common clinical scenarios. Methods: In 2018-2019, 24 US clinical labs each collected up to 100 RTI and 50 BSI consecutive gram-negative pathogens per year as part of the global SMART surveillance program. Only the 1195 Pa isolates collected from patients in ICU or non-ICU hospital wards were included in this report; 1078 and 117 isolates were from patients with RTI and BSI, respectively. MICs were determined using CLSI broth microdilution and breakpoints. Results: Susceptibility for P/T, FEP, and MEM was generally lower among isolates from patients in ICU than non-ICU wards by 5-14 percentage points, while the difference was ≤3 percentage points for C/T (Table). C/T maintained activity against 96% of ICU isolates, 17-23 percentage points higher than P/T, MEM, or FEP. MEM inhibited 40% of P/T-NS and 34% of FEP-NS ICU isolates, while C/T maintained activity against 81-88% of P/T-NS, FEP-NS, and MEM-NS isolates from ICU patients (Table, Figure). Results Table Conclusion: High co-resistance in Pa was seen with P/T, FEP, and MEM especially among ICU isolates. These data suggest that routine escalation to a carbapenem may not be optimal in some critically ill patients not responding to empiric therapy. Among the tested β-lactam antibiotics, C/T showed the highest activity against Pa isolates overall and among resistant phenotypes. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) C. Andrew DeRyke, PharmD, Merck & Co., Inc. (Employee, Shareholder) Kelly Harris, PharmD, BCPS, Merck & Co. Inc (Employee) Katherine Young, MS, Merck (Employee) Mary Motyl, PhD, Merck & Co., Inc. (Employee, Shareholder) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)